Kanamycin-Mediated Conformational Dynamics of Escherichia coli Outer Membrane Protein TolC - Pattanayak, Biraja S.; Dehury, Budheswar; Priyadarshinee, Mamali; Jha, Suman; Beuria, Tushar K.; Soren, Dhananjay; Mallick, Bairagi C. (Frontiers in Molecular Biosciences, 2021)
TolC is a member of the outer membrane efflux proteins (OEPs) family and acts as an exit duct to export proteins, antibiotics, and substrate molecules across the Escherichia coli cell membrane. Export of these molecules is evidenced to be brought about through the reversible interactions and binding of substrate-specific drug molecules or antibiotics with TolC and by being open for transport, which afterward leads to cross-resistance. Hence, the binding of kanamycin with TolC was monitored through molecular docking (MD), the structural fluctuations and conformational changes to the atomic level. The results were further supported from the steady-state fluorescence binding and isothermal titration calorimetry (ITC) studies. Binding of kanamycin with TolC resulted in a concentration dependent fluorescence intensity quenching with 7 nm blue shift. ITC binding data maintains a single binding site endothermic energetic curve with binding parameters indicating an entropy driven binding process. The confirmational changes resulting from this binding were monitored by a circular dichroism (CD) study, and the results showed insignificant changes in the α-helix and β-sheets secondary structure contents, but the tertiary structure shows inclusive changes in the presence of kanamycin. The experimental data substaintially correlates the RMSD, Rg, and RMSF results. The resulting conformational changes of the TolC-kanamycin complexation was stabilized through H-bonding and other interactions.